G. Hempel, Deductive-Nomological Vs. Statistical Explanation - Thomas M. Simpson (Crítica)
G. Hempel, "Deductive-Nomological Vs. Statistical Explanation", Minnesota Studies in the Philosophy of Science, vol. III, edited by H. Feigl and G. Marxwell, University of Minnesota Press, Minneapolis, 1962, pp. 98-169.